Aging oocytes: exploring apoptosis and its impact on embryonic development in common carp (Cyprinus carpio) - Konar, Essaikiammal Sodalai Muthu; Brachs, Sebastian; Mai, Knut; Waghmare, Swapnil Gorakh; Policar, Tomas; Samarin, Azadeh Mohagheghi; Samarin, Azin Mohagheghi (Journal of animal science, 2025)
Ovulation, fertilization, and embryo development are orchestrated and synchronized processes essential for the optimal health of offspring. Postovulatory aging disrupts this synchronization and impairs oocyte quality. In addition, oocyte aging causes fertilization loss and poor embryo development. This investigation aimed to unravel the endpoint of in vitro oocyte aging in common carp (Cyprinus carpio) to understand the involvement of apoptosis in postovulatory oocyte death. It was observed that the fertilization ability significantly declined (P < 0.001) at 8-h poststripping (HPS), subsequently triggering apoptosis in the advanced stage of oocyte aging, i.e., 48 HPS. This process included an increase in proapoptotic transcripts (fas, bax, cathepsin D, caspase 8, caspase 9, and caspase 3a) (P < 0.05), elevated levels of caspase 3 protein (P < 0.05), and activation of caspase 3 enzyme (P < 0.001), a key player in apoptosis, in aging oocytes. Furthermore, the effects of oocyte aging on the embryonic apoptosis machinery were examined in embryos at 5-h postfertilization (HPF) and 24 HPF derived from fresh and aged oocytes. Expression of apoptotic genes and caspase enzyme activity remained at the basal level in 5 HPF (early blastula embryos) from both fresh and aged oocytes. In contrast, the zymogenic and active forms of caspase 3 increased in 24 HPF embryos from 8-h-aged oocytes (P < 0.01) compared with those from fresh oocytes. Thus, apoptosis intensified in 24 HPF embryos from aged oocytes without affecting the apoptotic machinery of early blastula embryos. Our findings demonstrate that apoptosis initiated by the Fas/FasL system is an important physiological process accompanying oocyte aging in common carp.
Keywords: embryo nesavčí; Embryo, Nonmammalian; spontaneous activation; kaspasy; embryonální vývoj; kapři; Female; early blastula embryos; stárnutí; zvířata; Caspases; Aging; apoptosis; oocyty; apoptóza; Carps; Gene Expression Regulation, Developmental; Embryonic Development; ženské pohlaví; vývojová regulace genové exprese; Animals; in-vitro-aged oocytes; Oocytes; caspases; fish; Apoptosis